Weak One-Dimensional Field Confinement Silica Waveguides - Chenming Zhao; Lin Chen; Lei Xu; Liying Liu (IEEE Photonics Journal)
A novel weak one-dimensional field confinement silica waveguide (WCSW) with a large horizontal and vertical aspect ratio and low refractive index difference is proposed and fabricated via sol-gel technique. This new type of waveguide exhibits properties of high lithography tolerance, low polarization dependence, low propagation loss and low coupling loss with a single-mode fiber. More importantly, WCSW can provide extremely large evanescent field in vertical direction. The measured propagation loss and coupling loss are as low as 0.81 dB/cm and 0.71 dB/facet, respectively. In addition, high efficiency vertical coupling with a 1.9 μm gap between a WCSW bus waveguide and a WCSW based high Q (5.4 × 104) ring resonator is achieved, which demonstrates that vertical integration of WCSW is potentially applicable.